Pelatihan Pembuatan Pasta dan Bubuk Kaldu Jamur Tiram Bersama KWT Simbang Sejahtera - Andi Hermina Julyaningsih; Andi Nurfaidah Rahman; Arfina Sukmawati Arifin; Muhpidah Muhpidah; Fitri Fitri; Serli Hatul Hidayat; Sunrixon Carmando Yuansah (Universitas Methodist Indonesia, 2025)
KWT Simbang Sejahtera is one of the farmer groups in Simbang District that actively cultivates oyster mushrooms and markets them as fresh products to several suppliers in Maros Regency. Unfortunately, most of the profit from oyster mushroom production comes solely from the sale of fresh mushrooms. Instant seasonings in the form of powder or paste are widely used, both for household needs and the culinary industry, making them highly demanded in the market. The same applies to oyster mushroom broth, whether in powder or paste form. This community service activity aimed to train members of KWT Simbang Sejahtera to produce mushroom broth in paste and powder forms using their cultivated oyster mushrooms, in order to increase the added value and profits from their production. The training activity included several stages: pre-test, material presentation on oyster mushroom processing, practical session on making mushroom broth paste and powder, and a post-test. The pre-test results showed that 95% of participants did not know how to make mushroom broth powder, and 90% were unfamiliar with making mushroom broth paste. After the material delivery and hands-on practice, the post-test results showed that 100% of participants had learned how to make both broth powder and paste from oyster mushrooms. Based on these results, it can be concluded that this community service activity had a significant impact on participants’ understanding and knowledge.